Bank-based Investing Rotating Savings and Credit Associations for Islamic Finance. A New Alternative to Drain Households’ Savings and Reduce Financial Exclusion - HAMZAOUI, Moustapha; BOUSALAM, Issam (Journal of Advanced Studies in Finance; Vol 6 No 2 (2015): JASF Volume VI Issue 2(12) Winter 2015DO - 10.14505//jasf.v6.2(12).01, 2017)
This paper aims to conceptualize a new hybrid type of Rotating Savings and Credit Associations we called bank-based investing RoSCA. The model allows its members to invest their savings by means of the bank, and raise free-interest rate loans with no application and management fees. In fact, the conception of the bank-based RoSCA relied on the results of a survey questionnaire we administered among 725 subjects from different social categories in Morocco to comprehend the inherent features of this informal practice (RoSCA) locally called "Daret". By means of the two-way ANOVA (Analysis of the variance), we determined which social characteristics interact together to motivate a person to join a RoSCA. After all, we based on these findings to conceptualize the model taking into account both equity between members and sustainability of the operation. Unlike its counterparts, this model was designed to allow people with no prior cognition to be gathered by introducing the bank as a guarantor, and additionally, by withdrawing, temporarily, a deposit for default risk estimated by means of a risk-rating matrix we proposed. The model is also more attractive regarding its real economy promotion through investment, risk sharing process, and integration of financially excluded households.